How Thailand eliminated lymphatic filariasis as a public health problem - Sunsanee Rojanapanus; Tanaporn Toothong; Patcharida Boondej; Suwich Thammapalo; Naraporn Khuanyoung; Weena Santabutr; Preecha Prempree; Deyer Gopinath; Kapa D. Ramaiah (BMC, 2019)
Abstract Background Lymphatic filariasis is endemic in nine of the eleven Member States of the World Health Organization South East Asia Region. This article describes the intensive interventions with the National Programme for Elimination of Lymphatic Filariasis in Thailand since its launch in 2001 till the validation of its elimination in 2017. Methods A baseline epidemiological survey was initiated in 2001 to identify both brugian and bancroftian filarial areas and delineate its endemicity. Mass drug administration (MDA) with diethylcarbamazine citrate (DEC) and albendazole (ALB) was implemented in a total of 357 implementation units (IUs) in 11 lymphatic filariasis (LF) endemic provinces. The implementing unit (IU) was a sub-village. Stop-MDA surveys were conducted in 2006 in the 11 LF endemic provinces among population over 6 years of age and children of ≤6 years using immunochromatographic test (ICT) for Wuchereria bancrofti antigen and microfilariae (mf) detection for Brugia malayi. In Narathiwat province, Stop-MDA surveys were done in 2011 using ELISA. Transmission assessment surveys (TAS) were conducted in 2012-2013, 2015 and 2016-2017 among school students in the 6-7-year age-group. Surveillance of migrant populations through the national migrant health checkup were intensified in seven provinces over 2002-2017 for LF antigenaemia using ICT test cards. In four B. malayi endemic provinces, annual surveys to detect LF reservoir in domestic cats commenced in 1994. A 2001 survey of the chronic disease burden for LF established a register of the cumulative number of people with lymphedema/elephantiasis. Results A total of five rounds of MDA annually were implemented over 2002-2006 in all IUs. Additional annual rounds of MDA were required in 87 IUs of Narathiwat province from 2007 to 2011 due to persistent infection. The annual national drug coverage with MDA over 2002-2012 was in the range of 68.0 to 95.4%. Stop-MDA surveys in 2006 in the 11 LF endemic provinces found nine mf positive cases in seven IUs in Narathiwat province with the highest prevalence of 0.8% (range: 0.1-0.8%). In Narathiwat TAS-1, TAS-2 and TAS-3 detected below transmission threshold rates for B. malayi mf among antibody positive children (0.3, 0.2 and 0.7% respectively). Contact tracing both all mf cases in all three TAS yielded no positive cases. Through the migrant health checkup, a total of 23 477 persons were tested, showing a positive rate of 0.7% (range: 0.1-2.7%) over years 2002-2017. In Narathiwat province, annual ivermectin treatment among cats commenced in 2003 resulting in a decline of mf prevalence among cats from 8.0% in 1995 to 0.8% in 2015. As of April 2017, a total of 99 lymphoedema/elephantiasis patients were registered and followed-up under 34 health facilities. Conclusions Thailand over the years 2002 to 2011 conducted extensive MDA with high coverage rates. Through periodic and regular monitoring surveys it delineated LF transmission areas at sub-village level and demonstrated through its evaluation surveys - the Stop-MDA surveys and TAS, below transmission threshold rates that enabled its validation of LF elimination. In September 2017, World Health Organization acknowledged the Ministry of Health Thailand had eliminated lymphatic filariasis as a public health problem.